Efecto de ana y aib en la propagación por esqueje de mamey (Mammea americana l.)” En el cantón Quevedo - Zapatier Santillan, Aurelio David (2015)
The work it performed on the premises of the State Technical University Quevedo in Sto route. Sunday 1.5 kilometers in order to obtain genetically improved plants and high production relied on a system of vegetative propagation by cuttings method using hormones NAA and IBA, superior genotypes of Mamey (American Mammea L.) Quevedo, including indole-butyric acid (IBA) and naphthaleneacetic acid (NAA), 3000 mg dose. / L AIB + 3000 mg. / L ANA, 2500 mg. / L AIB + 2500 mg. / L ANA, 2000 mg. / L AIB + 2000 mg. / L ANA, 1500 mg. / L AIB + 1500 mg. / L ANA, and a control (without hormones) combined with substrate of soil, sand and rice husks are the treatments under study. One Completely Random Design (CRD) with 5 treatments, 4 replicates and 14 observations in experimental unit was used. At 45, 52 and 60 days the percentage of mortality, plant rooting percentage, number of roots, length of roots and plant costs, using the Tukey test to determine significant differences between treatments measures are evaluated . An analysis of the results and interpretation of experimental evidence is concluded that the treatment achieved the highest average number of roots was the T5 (3000 mg. / L AIB + 3000 mg) with 19,15 and root length was the T5 (3000 mg. / L AIB + 3000 mg) with 24.10. The average survival rate was between 47% and 45%. The highest average rooting was observed in the T4 (2500 mg. / L IBA + 3000 mg) 75.25% treatment and T5 (3000 mg. / L IBA + 3000 mg) with 75.25%. The treatment had the best performance was the T2 (1500 mg. / L AIB + 3000 mg) with 120.28% return.